Wear and friction properties of pineapple leaf fibers-reinforced natural rubber composites with the influence of multi-walled carbon nanotubes - Xuan, Yeo Yi; Ridzuan, M.J.M.; Abdul Majid, M.S.; Syayuthi, A.R.A.; Mat, Fauziah; Salit @ Sinon, Mohd Sapuan (John Wiley and Sons, 2024)
This study advances the creation of biocomposite materials and serves to reduce and utilize agricultural waste such as pineapple leaf fibers (PALF). In this study, PALF-reinforced natural rubber (NR) composites with included multi-walled carbon nanotubes (MWCNT) were analyzed and characterized at various fiber loadings. The PALF content was ranged from 0, 10, 20 to 30 parts per hundred rubber (phr) while the MWCNT content was maintained at 10 phr. A two-roll mill mixing process followed by molding was employed to fabricate the NR composites. Based on the curing behavior, tribological properties, and morphological analysis, it was confirmed that the hybrid reinforcement of the MWCNT and PALF improved the curing behavior, wear resistance, and morphology of the composites. The wear and friction properties of the composites namely coefficient of friction (COF), frictional force and specific wear rate (SWR) are significantly influenced by the applied loads. The COF of NR/30PALF and NR/30PALF/MWCNT composites is reduced to 0.80 and 0.72 respectively under 15 N of load. Physical properties namely the cross-link density and swelling behavior of the composites ranged from 3.70 × 10−4 to 5.71 × 10−4 mol/cm3 and 207.81 to 386.17%, respectively. According to the results obtained, the best cure and wear behavior followed by the morphological analysis are observed in NR/30PALF/MWCNT composite. Among the samples tested, NR/30PALF composite exhibited the best performance in both cross-link density and swelling behavior. It is anticipated that the findings of this study are expected to provide theoretical data for the design and optimisation of high-performance automotive and footwear applications. Highlights: NR/30PALF/MWCNT hybrid composite exhibited the shortest (Formula presented.) The addition of MWCNT improved the wear resistance of the composites The reinforcement of PALF at 30 phr possessed the lowest swelling ratio and the highest cross-link density of the composites The addition of MWCNT decreased cross-link density of the composites. © 2024 Society of Plastics Engineers.